A green cross-link strategy to rubber composites using water as a crosslinking agent. (12th April 2022) - Wang, Qianqian; Xu, Pengwu; Yang, Weijun; Liu, Tianxi; Hoch, Martin; Ma, Piming
Abstract: The current cross-link method in rubber industry is suffering from the utilization of toxic curing packages and the release of volatile organic compounds (VOCs). In this work, we propose a green cross-link route to make robust rubber materials. To prove this concept, ethylene-vinyl acetate-glycidyl methacrylate copolymer (EVM-GMA) functionalized with silane groups, i.e., EVM-Si(OC2 H5 )3 as a model rubber was firstly designed by solvent-free compounding. Then, the silane groups of EVM-Si(OC2 H5 )3 rubber are hydrolyzed and cross-linked with water molecules. The cross-link density, tensile strength and hardness of the EVM-Si(OC2 H5 )3 rubber increased gradually with temperature up to 200 °C. Subsequently, the water cross-linked EVM-Si(OC2 H5 )3 rubber was reinforced with silica (SiO2 ) that created a secondary network via an in situ interfacial reaction between the –OH groups of SiO2 and the silane groups of EVM-Si(OC2 H5 )3 . As a consequence, the SiO2 nanoparticles could be evenly dispersed in the rubber matrix with strong interfacial bonding. The tensile strength and elongation at break of the EVM-Si(OC2 H5 )3 /SiO2 nanocomposites reached to 10.0 MPa and 800%, respectively at a SiO2 loading of 30 phr. Thus, the new cross-link strategy addressed here may promote the development and application of rubber industry in some environmental-friendly domains. Graphical abstract: Image 1